CdH007 - Bairro da Pasteleira: conjunto habitacional das "Torres Vermelhas" | Pasteleira Housing Estate: "Torres Vermelhas" housing complex - Marta Rocha Moreira (2019)
Cadernos de Habitação n.º 007 - The CADERNOS DE HABITAÇÃO (CDH Portugal) emerged from a cooperation agreement between Mapping Public Housing · MdH (FAUP-CEAU/FCT), GIVCO (ETSAM-UPM) and PC3 (FAUUSP) researchers which led to the portuguese version of "Cuadernos de Viviendas", originally published by GIVCO - Grupo de Investigación en Vivienda Colectiva, with the supervision of the Main Research Prof. Carmen Espegel Alonso. The aim of this agreement is to systemize information on collective housing which will be made available to researchers, architects, public organizations and other interested parties.